RANCANG BANGUN SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB DI SMK NEGERI 5 BATAM - Boru Sitorus, Melani Krissa Delvi; Elisa, Erlin (Computer Science and Industrial Engineering, 2021)
Library is a collection of scientific books that are useful for humans. In schools, the library can be defined as a room that contains books to support every activities in school for students and teachers. The information in the library is also managed based on the educational needs of a school. The web-based library information system is the school's choice to simplify and shorten the time in data collection and other activities. This Library Information System was created using Odoo open source software and also with Unified Modeling Language tools. This software is also a business application that includes CRM (Custom Relationship Management). SMK Negeri 5 Batam requires a library information system as a tool to manage borrowing and returning data.